Slip distribution and source parameters of the 20 July 2017 Bodrum-Kos earthquake (Mw6.6) from GPS observations - Tiryakioglu; Aktug, B.; Yigit, Cemal Ozer; Yavasoglu, H.; Sozbilir, H.; Özkaymak; Poyraz, F.; Taneli, E.; Bulut, F.; Dogru, A.; Özener, H. (2018)
© 2017 The Author(s). Greek-Turkish boundary near the cities Kos and Bodrum has been shaken on July 20, 2017 by a Mw6.6 earthquake. The mainshock is located offshore and did not generate an on-land surface rupture. Analyzing pre- and post-earthquake continuous/survey-type static GPS observations, we investigated co-seismic surface displacements at 20 sites to characterize source parameters and slip-distribution of the mainshock. Fault plane solutions as well as co-seismic slip distribution have been acquired through the inversion of co-seismic GPS displacements modeling the event as elastic dislocations in a half space. Fault plane solution shows a southward dipping normaltype fault segment extending a depth down to ~12 km, which remains within the brittle upper crust. Results from the distributed slip inversion show that the mainshock activated a ~65 km fault section, which has three high slip patches, namely western, central and eastern patches, where the coseismic slips reach up to 13, 26, and 5 cm, respectively. This slip pattern indicates that the pre-earthquake coupling, which is storing the slip deficit, occurred on these three patches.